Pemrosesan Citra Side Scan Sonar untuk Pemetaan Dasar Laut Pelabuhan Benoa - Henry M. Manik; Liva Junaedi; Gentio Harsono (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2016)
Detection of seabed can be obtained with a high resolution using side scan sonar instrument. This instrument also provides geospatial information of underwater target. This paper aims are to visualize and to interpret side scan sonar imagery both qualitatively and quantitatively, to analyse acoustic backscatter of seabed, and to perform processing characteristics of sonar signal using wavelet transform. Side scan sonar data are processed through the geometric correction to establish the actual position in the image pixel. The location of research study is Benoa Port, Bali Indonesia. The sonar surveys consist of several track lines survey with operating frequency of 325 kHz. The seabed texture consists of gravel with backscatter value range from 13824 mV to 23680 mV and 8832 mV to 13312 mV for sand, sediment ripples of 17792 mV to 32640 mV, dredging seabed of 8000 mV to 19330 mV, texture of mound area has 32640 mV, and rocky outcrop has 14845 mV to 23552 mV. The results analysis of the signal characteristics using wavelet transform generally defines the location of peaks and valleys of the backscatter amplitude for each texture. The peak magnitude of each texture in red color indicates the intensity of the seabed texture is more rough, complex and solid, while the seabed texture is relatively flat and soft physic material has a low magnitude the value in blue color.